(untitled) (Abibisem: Journal of African Culture and Civilization, 2011)
Following the liberalisation of the airwaves in Ghana in the mid-1990s, the right to freedom of speech has been guaranteed although not without abuses. This freedom is evident in the activities of radio networks that urge listeners to participate in radio panel discussions (RPDs) through making interactive telephone calls or by posting text messages. In this paper, I explore the discourse of flaming on the panel discussions of Joy FM and Peace FM, two popular private radio stations. Grounded in Herring’s (2004) computer-mediated discourse analysis, the Judy shows that listeners of RPDs use SMS to deprecate other selves. The study also reveals that flaming is precipitated by such technological affordances of mobile telephony as anonymity, pseudonymy and facelessness. The analysis further shows that social dissatisfactions were more frequent on RPDs than political complaints. Based on these findings, the study recommends that media houses educate the public on the face threatening potential of the SMS technology, given that derisive messages undermine the social, cultural and national cohesion.